Miroblatta baai, a new very large cockroach species from caves of Borneo (Blattaria: Blaberidae) - Grandcolas, Philippe; Deharveng, Louis (Zootaxa, 2007)
A new species of the genus Miroblatta Shelford, 1906 is described from caves of Borneo in East Kalimantan, Indonesia. This new species, M. baai sp. nov., is similar to the epigean species M. petrophila Shelford, 1906 also found in Borneo. It differs by a larger adult size, longer legs, shorter wings, longer pronotum showing a remarkable central bulbous structure, lighter colouration and genital morphology (especially sclerite L1 shape). The genital morphology as well as morphological evidence for ovoviviparity confirm that the genus belongs to the family Blaberidae, subfamily Epilamprinae. Contrary to its epigean relative M. petrophila, this new species has been found exclusively in karstic caves of the same underground river system and these occurrences as well as the elongated legs and reduced eyes allow one to assume that this is a truly troglobitic species, so far the first one recorded in the family Blaberidae.